Before and After the Hartz Reforms: The Performance of Active Labour Market Policy in Germany - Lena Jacobi; Jochen Kluve (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
Having faced high unemployment rates for more than a decade, the German government implemented a comprehensive set of labour market reforms during the period 2003-2005. This paper describes the economic and institutional context of the German labour market before and after these so-called Hartz reforms.Focussing on active policy measures,we delineate the rationale for reform and its main principles.As results of programme evaluation studies post-reform have become available just now, we give a first assessment of the effectiveness of key elements of German ALMP before and after the Hartz reforms. The evidence indicates that the re-organisation of public employment services was mainly successful, with the exception of the outsourcing of services. Re-designing training programmes seems to have improved their effectiveness, while job creation schemes continue to be detrimental for participants? employment prospects. Wage subsidies and start-up subsidies show significantly positive effects.On balance, therefore, the reform seems to be moving the German labour market in the right direction.
Keywords: J0; J88; J68; 330; Active labour market policy; labour market reform; programme evaluation; Hartz laws